A study on the reversible photo-induced isomerisation of platinum(II) and palladium(II) complexes of the N,N-dialkyl-N’-acyl(aroyl)thioureas with reversed-phase HPLC separation from related rhodium(III), ruthenium(III) and iridium(III) complexes - Nkabyo, Henry Ane (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.